The voyage of the Dawn Treader - Lewis, C. S. (Clive Staples) 1898-1963.; Baynes, Pauline (Thorndike, ME Thorndike Press, 2001)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.
Originally published: New York : Macmillan, 1952. (Chronicles of Narnia ; bk. 5)
Keywords: Large type books; Fantasy; Large type books